Increasing Brace Treatment for Pediatric Distal Radius Buckle Fractures: Using Quality Improvement Methodology to Implement Evidence-based Medicine. Issue 8 (September 2019) - Little, Kevin J.; Godfrey, Jenna; Cornwall, Roger; Carr, Preston; Dolan, Kevin; Balch Samora, Julie
Abstract : Background: Multiple randomized trials have showed equivalent outcomes and improved patient/family satisfaction using a removable brace to treat pediatric distal radius buckle fractures (DRBF). We tested the hypothesis that we could use quality improvement (QI) methodology to increase the proportion of patients with DRBF treated with removable braces at 2 tertiary care orthopaedic clinics from a baseline of 34.8% to 80%. Methods: Clinic billing records were reviewed monthly to determine treatment (brace vs. cast) of DRBF and tracked using control charts (p-chart). Balance measures including correct application of the diagnostic criteria and algorithm were monitored. Process measures including the number of follow-up visits, radiographs obtained, and total cost of treatment were collected. Baseline data were obtained over a 3-month period, followed by a 12-month period of interventions using Plan-Do-Study-Act cycles targeting both individuals and groups of providers. Results: The proportion of DRBF treated in a brace increased from a combined baseline of 34.8% to a combined 84% at the end of the study period. Following intervention, 83% (15/18) of providers began using braces for a majority of patients (defined as >67%), with only 1 provider continuing to use casts 100% of the time. Patient preference was cited as the most common reason for use of cast treatment. There was a significant decrease in the number of radiographs obtained at 1 of 2 institutions. The charges for brace treatment averaged $630 less per patient than for cast treatment, leading to an estimated medical-cost savings of $205, 000 following intervention. Conclusions: Implementation of brace treatment for pediatric DRBF using QI methodology resulted in a shift toward brace treatment in the majority of patients, leading to substantial medical and nonmedical cost savings. Although patient preference was cited as the most common reason for persistent cast treatment, the data show the use of cast treatment to be more dependent upon individual provider preference. Level of Evidence: Level II—therapeutic. Abstract : Supplemental Digital Content is available in the text.